Creating web based communities using XML portals - Alves, Paulo (2010)
The fast growing of Internet in several domains, originates the appearance of numerous virtual communities, sometimes named Web based communities, of information and knowledge exchange. The adoption of Information and Communication Technologies (ICTs) in education and the creation of educational virtual communities don’t follow the growing of Internet in the other sectors. The success of virtual communities could be found on the facility to communicate, the easy access to resources and the continuous contribution of the members to the knowledge of the community. To be fully adopted in education is essential to change the educational paradigm and integrate ICTs in all the education and administration processes. This paper presents the principal conduct lines to develop Web based communities in higher education using XML Portals, integrating the several services and resources of the institution and promote the communication and knowledge exchange between students, teachers and staff.